PEMILIHAN BANK MENGGUNAKAN METODE ANALYTIC HIERARCHICAL PROCESS DENGAN PENDEKATAN DECISION SUPPORT SYSTEM - Akmaludin Akmaludin (Paradigma, 2010)
Many people are considering to invest his wealth in a way to save, but how to determine the proper selection of the Bank, of course there are considerations that a reference to determine the choice. Such as the type Bank whether the Bank of Conventional or Bank of Syariah, there is also view of other aspects such trusty, service, credibility, and promise.To determine the selection there is one application that can assist in decision-making process that is the expert choice application, this application has the same working principles with analytic hierarchical process. In principle, determine the eigen values vector is the most important and critical to the outcome of data analysis. If using AHP eigen values vector determination must be done repeatedly until there is no difference eigen values in each iteration, but with the application of expert choice it can be done more quickly, because it has been programmed in each iteration process. Once the eigen values vector is found then proceed by searching for value of Consistency Index (CI) and Consistency Ratio (CR).The analysis result computed by the application of expert choice eigen values vector obtained in conventional and syariah criteria is 0.667 and 0.333, while the eigen values vector sub criteria for trusty, service, credibility and promise for the conventional highest grades 0.571, 0.025, 0.083, and 0.044, while the value eigen values vector sub criteria that gets the highest score is 0.071, 0.019, 0.033, and 0.027. Analysis results for Consistency Index value is -1.333 and Consistency Ratio (CR) is -2.298, this proved that the decision is acceptable. Keywords : Bank, analytic hierarchical process, consistency index  consistency ratio, expert choice application.